Pengaruh Upah Minimum dan Tingkat Inflasi terhadap Pertumbuhan Ekonomi dan Tingkat Pengangguran Terbuka di Provinsi Banten - Yessi Tamba; Dian Novita Sari; Rizki Imam Maulana; Asnidar Asnidar; Ahmad Ridha (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This study aims to determine the effect of wages and inflation on economic growth and the open unemployment rate in Banten. This quantitative research uses secondary data sourced from the Central Statistics Agency (BPS) from 2011 - 2023. The data analysis used used the path analysis method. The results of this study indicate that the minimum wage directly has a negative and significant effect on economic growth in Banten Province. Inflation has a positive but insignificant effect on economic growth in Banten Province. Minimum wage has a negative and significant effect on the Open Unemployment Rate in Banten Province. Inflation has a negative and insignificant effect on the Open Unemployment Rate in Banten Province. Economic Growth has a positive but insignificant effect on the Open Unemployment Rate in Banten Province. Meanwhile, indirectly, Minimum Wage has a negative and significant effect on Open Unemployment Rate through Economic Growth in Banten Province. Inflation has a positive and insignificant effect on the Open Unemployment Rate through Economic Growth in Banten Province.